2019
DOI: 10.1017/s1431927619014909
|View full text |Cite
|
Sign up to set email alerts
|

Carrier-Transport Study of Gallium Arsenide Hillock Defects

Abstract: Single-crystalline gallium arsenide (GaAs) grown by various techniques can exhibit hillock defects on the surface when sub-optimal growth conditions are employed. The defects act as nonradiative recombination centers and limit solar cell performance. In this paper, we applied near-field transport imaging to study hillock defects in a GaAs thin film. On the same defects, we also performed near-field cathodoluminescence, standard cathodoluminescence, electron-backscattered diffraction, transmission electron micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…A better understanding of the carrier transport phenomena within real devices will generate knowledge that could possibly result in solar cells with higher efficiencies and greater stability. We have developed a near-field transport imaging (TI) technique to locally characterize charge carrier recombination in thin-film solar cells. Here, we applied the TI technique on the cross section of CdTe-based thin-film solar cells, allowing the direct visualization of carrier transport within the device both before and after degradation. We found that the carrier transport properties were significantly different between pristine and degraded cells, which could possibly be explained by Se interdiffusion toward the back-contact.…”
Section: Introductionmentioning
confidence: 99%
“…A better understanding of the carrier transport phenomena within real devices will generate knowledge that could possibly result in solar cells with higher efficiencies and greater stability. We have developed a near-field transport imaging (TI) technique to locally characterize charge carrier recombination in thin-film solar cells. Here, we applied the TI technique on the cross section of CdTe-based thin-film solar cells, allowing the direct visualization of carrier transport within the device both before and after degradation. We found that the carrier transport properties were significantly different between pristine and degraded cells, which could possibly be explained by Se interdiffusion toward the back-contact.…”
Section: Introductionmentioning
confidence: 99%